Bridging Performance and Preference: An Evaluation of Beringharjo Market Facilities Through IPA and Conjoint Methods - Anisa Nurpita; Bagaskara Bagaskara; Fatima Putri Prativi (Magister Ilmu Administrasi Publik, 2026)
This study employs a combined Importance Performance Analysis (IPA) and conjoint analysis to assess service attributes at Beringharjo Market. The IPA evaluation identifies a strategic roadmap: key strengths including ample parking, friendly vendors, secure shopping, appropriate quality, pricing, and accessible transportation fall in Quadrant I, indicating they meet visitor expectations and should be diligently maintained. Critical service gaps in Quadrant II such as cleanliness, toilet and trash bin availability, environmental comfort, signage, and digital payment systems (QRIS) require prioritized improvement to enhance visitor satisfaction. Conjoint analysis further reveals that environmental comfort is the most influential attribute, contributing approximately 31.26% to visitor preferences, while other features like clear signage, adequate toilets, QRIS, and rest areas hold secondary importance. The conjoint model demonstrates high predictive reliability (Pearson’s R = 0.979; Kendall’s Tau = 0.912, both p < 0.01), validating the findings. These results underscore the need for evidence-based, user-centered facility enhancements beginning with environmental comfort to bolster market appeal and visitor loyalty.